Stanovanjska gradnja v Sloveniji - Pust, Viktor (Urbani izziv, 2000)
The limited quantity of new housing in Slovenia and the recognised public interest for solving housing problems imply different procedures in providing houses for various social groups. The article presents present development issues concerning housing development in Slovenia. A competition project for the design of Sneberje, a suburban housing neighbourhood near Ljubljana, illustrates the issues.
Keywords: architecture; arhitektura; kvaliteta; prostorsko planiranje; Sneberje; spatial planning; stanovanjska gradnja; stanovanjske zgradbe; urbanistično planiranje